Optimization of Security Unit of Intelkam Raising in Overcoming the Spread of Radicalism in Kudus Resort - Alfarisyi, Muhammad Iqbal (Indonesian Journal of Police Studies, 2024)
The background of this research is the development of radicalism, especially right radicalism in Kudus Regency. Kudus Regency is a base for the development of radicalism because there are still many ex-convicts and their relatives who still have conflicting views with Pancasila. Efforts that can be made through unit IV of the security unit of the Kudus Police intelligence unit are to raise funds for the former convicts so that they can return in line with Pancasila. This study aims to examine and analyze the fundraising activities carried out by the security unit IV of the Kudus Police intelligence unit in tackling the spread of radicalism and the influencing factors. This research was carried out by the writer at the Kudus Police. The research was conducted using a qualitative approach using descriptive analysis techniques and using SWOT theory and 5M Management Theory and POAC. The results of the study show that there is still a discrepancy between the practice of fundraising in the field and the Regulation of the Head of the National Police’s Security Intelligence Agency No. 3 of 2013 which forms the basis for the implementation of the activities of the National Police’s intelligence intelligence unit. The implementation discrepancy, starting from the planning stage to the evaluation stage which has been arranged in Perkab No. 3 of 2013. This happened due to the existing field conditions. besides that there are still many shortages of existing resources both from a lack of personnel, the lack of ability to use existing resources, and poor organizational management. These obstacles make the fundraising in tackling radicalism not optimal.